Ionic/Electronic Dual‐Conductor Coating Layer Fabrication Enabling High‐Performance Silicon Anode. Issue 2 (1st December 2022) - Li, Liewu; Du, Baorong; Yang, Yizhao; Ye, Shenghua; Huang, Tao; Huang, Shaoluan; Ren, Xiangzhong; Hu, Jiangtao; Zhang, Qianling; Liu, Jianhong
Abstract : Silicon (Si) has received special attention from both scientific research and corporate development for overcoming the current energy density bottleneck. However, the severe volume change and violent interfacial reaction diminish the full benefits of Si material and hamper its direct commercial utilization. Particle pulverization and the companied ionic/electronic isolation are regarded as the intrinsic reason for performance attenuation. Hence, a strategy that can maintain both electronic and ionic conductance on Si anode during the electrochemical process is of great significant for performance improvement and future commercial promotion. Accordingly, an ionic/electronic dual‐conductor coating layer fabrication route is done by in situ building Li4 SiO4 fast ion conductor coating layer and implanting electron conduction network, labeled as Si@Li4 SiO4 /amorphous carbon (C)/carbon nanotubes (CNTs). Notably, the Si@Li4 SiO4 /C/CNT electrode delivers excellent long‐term cycling stability and prominent rate capability. These results demonstrate that the in situ‐formed fast ionic conductor coating layer facilitates the rapid Li + diffusion, and the 3D network structure constructed by CNTs and amorphous carbon (polyvinylpyrrolidone‐derived carbon) effectively reinforce the structural stability and keep the electrical connection for the electrode. This study provides an ionic/electronic dual‐conductor coating design concept for Si‐based anode materials. Abstract : The 3D network structure of Si@Li4 SiO4 /C/CNTs composite is successfully prepared by an in situ coating strategy. The formed fast ionic conductor coating layer facilitates the rapid Li + diffusion, and the 3D network structure constructed by carbon nanotubes (CNTs) and amorphous carbon (PVP‐derived carbon) effectively reinforce the structural stability and keep the electrical connection for the electrode.